2019
DOI: 10.21037/atm.2019.07.103
|View full text |Cite
|
Sign up to set email alerts
|

The pathways and mechanisms of muramyl dipeptide transcellular transport mediated by PepT1 in enterogenous infection

Abstract: Background: The transcellular transport of muramyl dipeptide (MDP) mediated by peptide transporter (PepT1) involves the translocation into intestinal epithelial cell (IEC) stage and the transport out of IEC stage. However, its mechanism has not been fully understood. This study aimed to investigate the pathways and mechanisms of MDP transcellular transport in enterogenous infection.Methods: Firstly, experimental rats were randomly divided into three groups: sham-operation (sham group), MDP perfusion (MDP group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the IL-6 level was significantly higher in the 15 mg/kg MDP+LPS group than in the 1.5 mg/kg MDP+LPS group. The lung microbiome in a sepsis mouse model is enriched with intestine-associated bacteria (23), and the lung tissues of rats collected after enema with MDP have elevated NOD2 protein expression and increased lung injury (9). Therefore, the effects of MDP are not limited to the intestine; they can be elicited through PepT1 in the intestinal epithelium, crossing the intestinal mucosal barrier into the mesenteric lymph nodes and portal system, followed by circulation in the body to distant organs, such as the lungs, where NOD2 recognizes MDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the IL-6 level was significantly higher in the 15 mg/kg MDP+LPS group than in the 1.5 mg/kg MDP+LPS group. The lung microbiome in a sepsis mouse model is enriched with intestine-associated bacteria (23), and the lung tissues of rats collected after enema with MDP have elevated NOD2 protein expression and increased lung injury (9). Therefore, the effects of MDP are not limited to the intestine; they can be elicited through PepT1 in the intestinal epithelium, crossing the intestinal mucosal barrier into the mesenteric lymph nodes and portal system, followed by circulation in the body to distant organs, such as the lungs, where NOD2 recognizes MDP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the degree of pathological damage was higher in rats infused with MDP in the small intestine than in the control group, as were the expressions of signaling molecules (i.e., NOD2 and RIP2) and inflammatory mediators (i.e., myeloperoxidase, IL-8, and TNF-α). However, competitive inhibition of PepT1 function with short peptide enteral nutrition (SPEN) decreased the degree of MDP-induced intestinal injury, NOD2 and RIP2 mRNA expression, and the levels of inflammatory factors (9). Thus, MDP can cause bacterial product translocation through PepT1 intracellular transport, and SPEN competitively binds PepT1 with MDP, attenuating the intestinal inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent procedures were conducted as per the kit instructions. The optical density (OD) value at a wavelength of 450 nm was measured [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dietary proteins are cleaved into oligopeptides in the lumen and further processed into small peptides (dipeptides and tripeptides) and free amino acids (FAA). Ma GG et al constructed a mouse model, and conducted haematoxylin and eosin (HE) staining, enzyme‐linked immunosorbent assay (ELISA) and other experimental studies to show that PEPT1 (SLC15A1), a high‐capacity/low‐affinity peptide transporter, can achieve proton coupling absorption of more than 8000 different dipeptides and tripeptides, a variety of peptide‐like compounds are also PEPT1 transport substrates, including specific immune stimulants, angiotensin‐converting enzyme inhibitors and β‐lactam antibiotics 14,15 . The peptides in IECs are further hydrolyzed to FAA, and a small part of the absorbed oligopeptides are transported out by the H + ‐dependent peptide transport system on the basement membrane.…”
Section: Mechanisms Of Nutrients Absorption In the Intestinementioning
confidence: 99%